Interview with Professor Ram Bahadur Chhetri - Khattri, Man Bahadur; Subedi, Madhusudan; Rayamajhi, Durlav; Gurung, Bishnu (Dhaulagiri Journal of Sociology and Anthropology, 2024)
Professor Ram Bahadur Chhetri was born in Dehradun, India, on April 4, 1952. He comes from a military and peasant socio-cultural background. After completing his high school education in Nagaland, India, he received his Intermediate and Bachelor’s degrees at Prithvi Narayan Campus in Pokhara, Nepal. He was initially enrolled in the Master’s in Political Science program at the Central Department of Political Science at Tribhuvan University, Kirtipur, Nepal. However, circumstances led him to earn an MA in Anthropology from Pune University in Maharashtra, India, in 1980. He eventually earned a PhD from the University of Hawaii, USA, in 1990.